Radiology and the law : malpractice and other issues / Ronald Eisenberg ; foreword by John J. Smith, foreword by William T. Thorwarth, Jr. - Eisenberg, Ronald L. (Springer, 2004)
Practically every radiologist would benefit from an all-encompassing guide to malpractice issues in radiology. Dr. Ronald Eisenberg, a highly respected author in the field, has put together a comprehensive reference to provide radiologists with an introduction to malpractice issues and a basic understanding of their relationships with government regulatory agencies and HMOs. This softcover book will detail the mechanics of a lawsuit, how radiologists can become the object of a malpractice action, and what they can do to minimize potential exposure. (Publisher's Description).